THE INFLUENCE OF CONSUMER BEHAVIOR AND DIGITAL MARKETING ON PURCHASE DECISION AT GRABFOOD IN MANADO - Sigar, Endah T.; Massie, James D.D.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2021)
The development of information technology and communication takes place very quickly and covering all aspects in human life. This all digital technology trend helps humans in carrying out their daily activities starting from the existence of digital devices, applications and the internet as well as various other innovations. This shown by the presence of online food delivery services. The purpose of this research is to analyze the influence of consumer behavior (cultural, social, personal, and psychological) and digital marketing (social media marketing, e-mail marketing, and search engine marketing) towards consumer purchase decision on GrabFood in Manado partially and simultaneously. Sample determined at 100 consumers. Tools of analysis using Multiple Linear Regression, hypothesis test using F test and T test. The result of research shows that consumer behavior and digital marketing simultaneously have significant influence towards consumer purchase decision. In partially consumer behavior have significant influence towards consumer purchase decision, while digital marketing do not have significant influence towards consumer purchase decision. The management of GrabFood suggested organizing a consultation program for MSME actors to participate in business incubation that can support their business progress through coaching for local businesses in facing the digital era, in order to increase the sales in ManadoÂ Keywords: consumer behavior, digital marketing, purchase decision, covid-19 pandemic.